The effects of volatile anesthetics and propofol in patients undergoing off-pump coronary artery bypass grafting: a systematic review and meta-analysis - Zhang, Chenghong; He, Changlin; Chen, Zhengwei; Chen, Xin; Qin, Junjun; Xu, Yuhui; Ma, Jiasen (Frontiers in Cardiovascular Medicine, 2023)
Background: Studies investigating the cardioprotective effect of volatile anesthetics on cardiac troponins in off-pump coronary artery bypass grafting (OPCAB) surgery remain controversial. This current study was conducted to systematically evaluate the impact of volatile anesthetics and propofol on patients undergoing OPCAB surgery.A computerized search of electronic databases was conducted up to July 21, 2023, to identify relevant studies using appropriate search terms. The primary outcomes of interest were the levels of myocardial injury biomarkers (e.g., cTnI, cTnT), while secondary outcomes included extubation time, length of ICU stay, 30-day mortality, transfusion and thrombosis, and postoperative recovery, which were compared between two anesthesia techniques.Results: A search of databases produced 14 relevant studies with a combined total of 703 patients. Among them, 355 were allocated to the volatile anesthetics group and 348 to the propofol group. Our study reveals a statistically significant reduction in myocardial injury biomarkers among patients who received volatile anesthetics compared to those who received propofol (P <.001). Subgroup analysis showed that patients using sevoflurane had lower postoperative cardiac troponins levels compared to propofol (P =.01). However, desflurane and isoflurane currently have no significant advantage over propofol (all P >0.05). There was no significant difference in postoperative mechanical ventilation time, length of ICU stay, and mortality between the two groups (all P >0.05).This study suggested that volatile anesthetics, specifically sevoflurane, in adult OPCAB surgery provide a better cardioprotective effect than propofol.